The impact of drive leg impulse and slope on throwing velocity and kinematics in the competitive throwing athlete - Glover, M. A.; Mylott, J. A.; Gaba, A.; Recker, A. J.; Bullock, G. S.; Waterman, B. R.; Nicholson, K. F. (Sports Health: A Multidisciplinary Approach, 2025)
Background Multiple studies have analyzed pitching kinematics using motion analysis technology, but lower extremity drive leg impulse (DLI) and drive leg slope (DLS) are not as well characterized. The purpose of this study was to investigate associations between DLI and DLS and pitch velocity as well as angular velocity of the pelvis, trunk, and humerus.